Association of parental HLA-G polymorphisms with soluble HLA-G expressions and their roles on recurrent implantation failure: A systematic review and meta-analysis - Hu, Lian; He, Dongmei; Zeng, Hong (Frontiers in Immunology, 2022)
Introduction HLA-G plays a central role in immune tolerance at the maternal-fetal interface. The HLA-G gene is characterized by low allelic polymorphism and restricted tissue expression compared with classical HLA genes. HLA-G polymorphism is associated with HLA-G expression and linked to pregnancy complications. However, the association of parental HLA-G polymorphisms with soluble HLA-G (sHLA-G) expression and their roles in recurrent implantation failure (RIF) is unclear. The study aims to systematically review the association of HLA-G polymorphisms with RIF, the association of sHLA-G expression with RIF, and the association of HLA-G polymorphisms with sHLA-G expressions in patients attending in-vitro fertilization (IVF) treatment. Methods Studies that evaluated the association of HLA-G polymorphisms with RIF, the association between sHLA-G expression with RIF, and the association between HLA-G polymorphisms with sHLA-G expressions in patients attending IVF treatment were included. Meta-analysis was performed by random-effect models. Sensitivity analysis was performed by excluding one study each time. Subgroup analysis was performed based on ethnicity. Results HLA-G 14bp ins variant is associated with a lower expression of sHLA-G in seminal or blood plasma of couples attending IVF treatment. The maternal HLA-G*010101 and paternal HLA-G*010102 alleles are associated with RIF risk compared to other alleles. However, single maternal HLA-G 14bp ins/del polymorphism, HLA-G -725 C>G/T polymorphism, or circulating sHLA-G concentration was not significantly associated with RIF in the general population. HLA-G 14bp ins/ins homozygous genotype or ins variant was associated with a higher risk of RIF in the Caucasian population. Discussion Specific HLA-G alleles or HLA-G polymorphisms are associated with sHLA-G expression in couples attending IVF treatment. Several HLA-G polymorphisms may be related to RIF, considering different ethnic backgrounds. A combined genetic effect should be considered in future studies to confirm the association of HLA-G polymorphisms and sHLA-G expressions in relation to RIF.